Prevalence and determinants of micronutrient deficiencies in malnourished older hospitalized patients - Kübra Yilmaz; Rainer Wirth; Diana Daubert; Maryam Pourhassan (Elsevier, 2024)
Background and objective: Malnutrition and micronutrient deficiencies represent significant concerns in geriatric care, leading to adverse health outcomes in older adults. The study aimed to investigate the prevalence and determinants of micronutrient deficiencies in malnourished older hospitalized patients. Design and setting: This prospective, observational study was conducted in a geriatric acute care unit. Participants: The study included 156 malnourished older adults. Measurements: Malnutrition was identified using the Mini Nutritional Assessment-Short Form. Micronutrient status was assessed through serum analysis of vitamins (A, B1, B6, B12, C, D, E, H, K, folic acid) and minerals (iron, zinc, copper, selenium) within 24 h post-admission. Results: The average patient age was 82.3 ± 7.5 years, with 69% female. The results revealed a high prevalence of micronutrient deficiencies, with 90% of patients exhibiting deficiencies in three or more micronutrients. Notably, every patient presented at least one micronutrient deficiency. Common deficiencies were found in vitamins C (75%), D (65%), H (61%), and K (45%), as well as folic acid (37%), iron (31%), zinc (36%) and selenium (35%). In binary regression analysis, the amount of previous weight loss was significantly associated with a higher prevalence of multiple (>2) micronutrient deficiencies (P = 0.045). Other variables such age (P = 0.449), gender (P = 0.252), BMI (P = 0.265) and MNA-SF score (P = 0.200) did not show any significant association with the prevalence multiple micronutrient deficiencies. Conclusion: The high prevalence of micronutrient deficiencies in malnourished older hospitalized patients underscore the urgent need for targeted interventions to address micronutrient deficiencies in this population, promoting their health status.